Adaptive differential amplitude pulse-position modulation technique (DAPPM) using fuzzy logic for optical wireless communication channels - Bong, Siaw Wee (2012)
In the past few years, people have become increasingly demanding for high transmission rate, using high-speed data transfer rate, the number of user increased every year, therefore the high-speed optical wireless communication link have become more popular. Optical wireless communication has the potential for extremely high data rates of up to tens of Gigabits per second (Gb/s). An optical wireless channel is usually a non-directed link which can be categorized as either line-of-sight (LOS) or diffuses. Modulation techniques have attracted increasing attention in optical wireless communication, therefore in this project; a hybrid modulation technique named Differential Amplitude Pulse-Position Modulation (DAPPM) is proposed to improve the channel immunity by utilizing optimized modulation to channel. The average symbol length, unit transmission rate, channel capacity, peak-to-average power ratio (PAPR), transmission capacity, bandwidth requirement and power requirement of the DAPPM were determined and compared with other modulation schemes such as On-Off Key (OOK), Pulse-Amplitude Modulation (PAM), Pulse-Position Modulation (PPM), Differential Pulse-Position Modulation (DPPM), and Multilevel Digital Pulse Interval Modulation (MDPIM). Simulation result shows that DAPPM gives better bandwidth and power efficiency depending on the number of amplitude level (A) and the maximum length (L) of a symbol. In addition, the fuzzy logic module is developed to assist the adaptation process of differential amplitude pulse-position modulation. Mamdani fuzzy logic method is used in which the decisions made by the system will be approaching to what would be decided by the user in the real world.